2011
DOI: 10.1080/15459624.2011.555258
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Use of Conventional Devices and Safety Device Activation Rates in Hospitals in Ontario, Canada

Abstract: This study assessed voluntary compliance with the use of sharp safety devices in lieu of conventional ones and the activation status of these safety devices: VanishPoint syringes, Terumo Surshield butterflies, and Insyte Autoguard IV catheters. Sharps disposal containers from various wards in three private, not-for profit, university-affiliated Ontario hospitals were audited during 9 days in August 2007. In the 149 audited sharps containers, 55% of all syringes found were conventional compared with 45% that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…18 Based on BBP transmission risk, Stringer and Haines proposed that an 'acceptable' phlebotomy and IV SED activation rate should be 100% or close to it, whereas syringe SED activation rates should be 90% or greater. 8 Such activation levels were not evident in this study. Accepting that not all procedures have SED available, and that education is essential in SI prevention, the dependence on manual activation of SED plays a major part in SI.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…18 Based on BBP transmission risk, Stringer and Haines proposed that an 'acceptable' phlebotomy and IV SED activation rate should be 100% or close to it, whereas syringe SED activation rates should be 90% or greater. 8 Such activation levels were not evident in this study. Accepting that not all procedures have SED available, and that education is essential in SI prevention, the dependence on manual activation of SED plays a major part in SI.…”
Section: Discussioncontrasting
confidence: 62%
“…15 Following SED legislation in Canada the non-SED syringe proportion was shown to drop from 56 to 7%. 8,10 However, SED-specific legislation is not the complete answer. This is illustrated by the fact that following the immediate reduction in SI with the SED law in the USA, 15 the incidence of SI has failed to fall further in the decade since, 1 and a similar pattern was documented immediately following SED legislation in British Columbia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The true SEIC adoption rates may be lower than those reported as suggested by previous studies in settings where both SEICs and traditional catheters were available. 39 In conclusion, implementing safety-engineered medical devices is a key component to reducing BBP transmission among health care workers. Canadian pediatric anesthesiologists are increasingly adopting SEICs in provinces where they are legislated.…”
Section: Discussionmentioning
confidence: 99%
“…3 It is important to note, however, that SESDs will still cause a residual fraction of injuries. Although these residual injuries occur most frequently during use of the item or during activation of the safety mechanism, 4 Mendelson 5 found that 21% of injuries from SESDs occur after use when an available but unengaged SESD could have prevented the injury. Activation rates of SESDs described in the literature range from 17% to 98% depending on the facility in which the devices were implemented and the type of device used.…”
Section: Infect Control Hosp Epidemiol 2012;33(8):842-844mentioning
confidence: 99%